Analisa Traksi Untuk Kendaraan Truk Angkutan Barang Jalur Denpasar-Gilimanuk - Chatur Adhi, IGAK; Komaladewi, AAIA Sri; Atmika, IKetut Adi; Suriadi, IGAK (Universitas Mataram, 2012)
Road condition and plain all of the line traffic Denpasar- Gilimanuk have many slope upward. Beside of many slope upward declivity and long slope upward have many variation too. We must give many attention for that condition in design minimum power engine to vehicle truck,beside the other factors like wind velocity , kind of asphalt , curves ,etc. The purpose of this research to recite road condition (slope upward , wind velocity ,density) all of the line traffic Denpasar – Gilimanuk,and then will be count minimum traction need of vehicle truck that across that road. From this research result obtained that the needed traction to overcome all resistance especially slope upward resistance are 6000 N and the estimate needed power about 220 hp from characteristic power torsi.